2019
DOI: 10.47678/cjhe.v49i3.188529
|View full text |Cite
|
Sign up to set email alerts
|

Policy Analysis of Equity, Diversity and Inclusion Strategies in Canadian Universities – How Far Have We Come?

Abstract: Institutional efforts to address equity, diversity and inclusion in educational settings have been often met with overwhelmingly critical accounts pointing towards well-intentioned attempts that have reinforced exclusion and inequity. A new wave of recent developments among Canadian research-intensive universities (U15) is providing a slightly different account of universities’ involvement in addressing the needs of equity-seeking students. This paper presents data collected through policy analysis of 50 strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 30 publications
0
32
0
5
Order By: Relevance
“…The Athena SWAN charter framework has been established in modified forms in other places, such as Australia (Science in Australia Gender Equity, SAGE-Athena SWAN); the USA (See change with STEMM Equity Achievement, SEA-Change and NSF ADVANCE); and, Canada (DIMENSIONS: Equity, diversity and inclusion) [41]. Canadian EDI efforts in universities are guided by the "Canadian Multiculturalism Act (1988), the Charter of Rights and Freedoms (1982), the Employment Equity Act (1986, revised in 1996) and the Canadian Human Rights Act (1977)" [19] (p. 43). The concept of employment equity was introduced in Canada by the 1984 Royal Commission on Equality in Employment [42], which focused on four groups: "women, persons with disabilities, Indigenous peoples and members of visible (or racialized) minorities" [43] (p. 6).…”
Section: Introductionmentioning
confidence: 99%
“…The Athena SWAN charter framework has been established in modified forms in other places, such as Australia (Science in Australia Gender Equity, SAGE-Athena SWAN); the USA (See change with STEMM Equity Achievement, SEA-Change and NSF ADVANCE); and, Canada (DIMENSIONS: Equity, diversity and inclusion) [41]. Canadian EDI efforts in universities are guided by the "Canadian Multiculturalism Act (1988), the Charter of Rights and Freedoms (1982), the Employment Equity Act (1986, revised in 1996) and the Canadian Human Rights Act (1977)" [19] (p. 43). The concept of employment equity was introduced in Canada by the 1984 Royal Commission on Equality in Employment [42], which focused on four groups: "women, persons with disabilities, Indigenous peoples and members of visible (or racialized) minorities" [43] (p. 6).…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this, all PSTs should get familiar with inclusive education and its core values, and as such understand the principles of equity and equality included in the CRPD. It is also important for teachers to gain disability-related knowledge and skills as well as strategies to work in inclusive settings (Majoko, 2017;Dally et al, 2019;Tamtik and Guenter, 2019). Furthermore, to promote inclusive education, the education of PSTs must integrate issues related to special education.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this model maintains that discriminating against disabled people should be seen as legally and ethically wrong (Degener, 2016(Degener, , 2017. Tamtik and Guenter (2019) reported that although equity, diversity, and inclusion have become the focus of numerous Canadian higher education institutions in recent years, there is still much work to do in terms of access and equity. For example, the Canadian Association for University Teachers (2019) estimated that 20% of academic staff have a dis/ability.…”
Section: Disability Modelsmentioning
confidence: 99%